Linguistic studies in Phoenician : in memory of J. Brian Peckham - Holmstedt, Robert D.; Peckham, Brian, 1934-2008 (Eisenbrauns, 2013)
Linguistic Studies in Phoenician: In Memory of J. Brian Peckham honors the late Professor J. Brian Peckham, a scholar who has been instrumental in furthering the cause of Phoenician studies over the past decades. His passion made him an exceptional teacher, and his research on Phoenician studies resulted in his Phoenicia: Episodes and Anecdotes from the Ancient Mediterranean (Eisenbrauns, 2014), which he finished just prior to his passing in September 2008.This collection of studies dedicated to his memory is aimed at advancing our understanding of the grammatical and historical features of the Phoenician language, a favorite topic that Professor Peckham rigorously studied and taught. The first set of studies concentrates on linguistic features of Phoenician qua Phoenician. They include investigations of phonology and morphology, as well as linguistic approaches to syntax and text-level pragmatics. The second set of studies seeks to situate aspects of the Phoenician language typologically or within comparative, etymological, and historical Semitics. The result is a group of studies covering topics ranging from case endings, negation, pronominal usage, and phonology to dialectology, etymologies, and text linguistics. Given the use of Phoenician throughout the Mediterranean littoral, this volume contains something of interest for numerous areas of investigation, including comparative Semitics, Anatolian, early Mediterranean, and even Hebrew and biblical studies.